Methodological aspects of patient safety culture research: A scoping Review - Pol, Thaiane Almeida S.; Figueiredo, Karla Crozeta; Portella, Patricia Cardoso; Figueredo, Alda Souza; Bicalho, Cleide Straub da Silva (Saúde (Santa Maria), 2021)
Investigating the safety culture has been relevant for more than two decades as a tool to improve the quality of patient care. This is a scope review of the last 20 years, whose objective is to investigate the type and prevalence of methodological approaches to patient safety culture and climate research. A review protocol was registered. The results were reported according to reports of preferred items for systematic reviews and extension of meta-analyzes for scope reviews (PRISMA-ScR). 107 studies were included. From the results, three major themes emerged for discussion, and the studies were classified into 1) Methodological approach and indeterminate use of concepts of climate and safety culture; 2) The isolated use of self-administered questionnaires in safety culture surveys and 3) A survey of the mixed methods approach in patient safety culture research. The quantitative approach was shown to be predominant, with the use of self-administered questionnaires for studies of the climate and culture of patient safety. The studies pointed out several limitations in the exclusive use of questionnaires, emphasizing the need to include multimethod research and the use of qualitative data collection techniques as an essential complement for the diagnosis of the patient safety culture.